Pesan Dakwah Gus Mus dalam Acara Percik Tahun 2017-2019 - Binti Qumairoh; Mimi Maolani (IAI Darussalam, 2021)
Gus Mus is a Muslim scholar, and also an artist, a writer, a politician, a cultural observer at once. His communicant has various backgrounds in those fields. His communication messages could contain da’wah messages or it’s not. His da’wah contents will show his da’wah characteristic which is not only as a Muslim scholar but also as other professions that had been mentioned above. This research is describing Gus Mus’s da’wah messages in the Percik program on Youtube GusMus’s Channel in 2017-2019. This research used the descriptive quantitative content analysis method. Data that was used are 18 videos of Gus Mus’s Islamic lecture in that program from 2017-2019. The data collection technique used a coding sheet filled out by three judges. The result of this research shows, there is a da’wah communication message about morals is 59%, faith is 23% dan sharia is 18%. The characteristic of Gus Mus’s da’wah messages was dominated by messages of humanity morals which is a call for universal kindness, which means a call to behave gently to others, da’wah with a good way and not forcing, remind each other for kindness and stay away from badness, do fair, and fond of compassion and good relationship than hates and disunity.